The Role of Enriched Microbial Consortium on Iron-Reducing Bioaugmentation in Sediments - Pan, Yuanyuan; Yang, Xunan; Xu, Meiying; Sun, Guoping (Frontiers in Microbiology, 2017)
Microbial iron reduction is an important biogeochemical process and involved in various engineered processes, including the traditional clay dyeing processes. Bioaugmentation with iron reducing bacteria (IRB) is generally considered as an effective method to enhance the activity of iron reduction. However, limited information is available about the role of IRB on bioaugmentation. To reveal the roles of introduced IRB on bioaugmentation, an IRB consortium enriched with ferric citrate was inoculated into three Fe(II)-poor sediments which served as the pigments for Gambiered Guangdong silk dyeing. After bioaugmentation, the dyeabilities of all sediments met the demands of Gambiered Guangdong silk through increasing the concentration of key agent (precipitated Fe(II)) by 35%, 27% and 61%, respectively. The microbial community analysis revealed that it was the minor species but not the dominant ones in the IRB consortium that promoted the activity of iron reduction. Meanwhile, some indigenous bacteria with the potential of iron reduction, such as Clostridium, Anaeromyxobacter, Bacillus, Pseudomonas, Geothrix and Acinetobacter, were also stimulated to form mutualistic interaction with introduced consortium. Interestingly, the same initial IRB consortium led to the different community successions among the three sediments and there was even no common genus increasing or decreasing synchronously among the potential IRB of all bioaugmented sediments. The Mantel and canonical correspondence analysis showed that different physiochemical properties of sediments influenced the microbial community structures. This study not only provides a novel bioremediation method for obtaining usable sediments for dyeing Gambiered Guangdong silk, but also contributes to understanding the microbial response to IRB bioaugmentation.